Techniques and resources in teaching grammar (Teaching Techniques in English as a Second Language) Marianne Celce-Murcia, Sharon Hilles; series editors Russell N. Campbell, William E. Rutherford - Celce-Murcia M.; Hilles S.; Campbell R. N.; Rutherford W. E. (Hong Kong Oxford University Press, 1988)
The first two chapters of the book address general questions of grammar in ESL theory and classroom practice. These are followed by ideas for the creative teaching of grammar. Included are specific suggestions for teaching most of the common, beginning-level structures, which are listed separately in a grammar index for easy reference.
Keywords: 811.111